Sistem Bagi Hasil Penggarapan Sawah di Desa Bedegung Kecamatan Semidang Aji (Studi Kasus Desa Bedegung Kecamatan Semidang Aji Kabupaten OKU) - Mauliyanti, Anita (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2020)
The aim of this research is to study the profit sharing in the rice cultivation system and study the perspective of Islamic law on the results in the rice cultivation system in Bedegung Village, Semidang Aji District, Ogan Komering Ulu Regency. This research is a qualitative research. The data sources used in this study are two, namely primary data and secondary data. The research location was in Bedegung Village, Semidang Aji District, Ogan Komering Ulu Regency for 60 days. Data collection techniques used in this study were interviews, observation, and documentation. Profit sharing in the system of cultivating paddy fields in Bedegung Village, Semidang Aji District, Ogan Komering Ulu Regency is known as Paruan where the land owner connects the land to the cultivator to be cultivated with the help of flowers) while the cultivators get one (1) part. If the fund is cultivated, then the portion gets 2 parts while the land owner gets 1 part. Likewise, the costs are borne jointly, then the portion obtained between the land owner and each tiller (1/2). From the perspective of Islamic law the Profit Sharing System in Cultivation of Rice Fields is not appropriate because it contains ghororic elements. The lack of clarity requested was the muzara'ah contract and mukhabarah regarding the contract agreement, because the landowners and tenants were not present in the agreement and the results of the agreement were not only written verbally. However, it is incomplete with Islamic law because the practice carried out by the Bedegung Village community is carried out on the basis of liking and liking unpleasant to help,